Demokrasi Ersatz: Menggugat Peran Pemuda dalam Mengawal Proses Demokratisasi di Indonesia - mahathir muhammad iqbal (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2015)
We already are in an open democratic stage within 17 years . However , we are also required to continue to make serious resolutions and improvements related to the character of the ideology of democracy . In many ways , we still fail to open up possibilities and alternatives in managing circulation prospective leadership and in accordance with the requirements of democracy . Fundamental changes to equip democracy needs to be done for the sake of the birth of the benefit shared values ​​. In this context, youth should play a role . youth should proofread and guarding the democratic process in order not to handcuffed by pragmatic political interests . Moreover, if we depart from the conviction , that the youth are the leaders of future generations. Permalink/DOI: http://dx.doi.org/10.15408/sd.v2i2.2817